Animal spirits in the beautiful game. Testing social pressure in professional football during the COVID-19 lockdown - Cueva, C. (2020)
The COVID-19 pandemic forced almost all professional football matches worlwide to be played in empty stadiums. This large-scale natural experiment offers a unique opportunity to assess the impact of social pressure on decision making and behavior. Using a large dataset from 41 professional football leagues in 30 different countries, I find that the home advantage in match outcomes drops by around one half and that referee bias against away teams disappears following the lockdowns. My results therefore suggest that social pressure exerted by home crowds has an important e ect on the behavior of referees and on game outcomes.